When immune cells turn bad: tumor-associated microglia/macrophages in glioma - Rösch, Saskia; Rapp, Carmen; Dettling, Steffen; Herold-Mende, Christel (International journal of molecular sciences, 2018)
As a substantial part of the brain tumor microenvironment (TME), glioma-associated microglia/macrophages (GAMs) have an emerging role in tumor progression and in controlling anti-tumor immune responses. We review challenges and improvements of cell models and highlight the contribution of this highly plastic cell population to an immunosuppressive TME, besides their well-known functional role regarding glioma cell invasion and angiogenesis. Finally, we summarize first therapeutic interventions to target GAMs and their effect on the immunobiology of gliomas, focusing on their interaction with T cells.